Three CBD stents removed: a rare case of obstructive jaundice - Bajwa, Jaspreet S.; Chaudhary, Rahul; Singh, Anjali (International Surgery Journal, 2025)
Retained biliary stents are a rare but important cause of obstructive jaundice and cholangitis. Authors reported a unique case of a 28-year-old female with three retained common bile duct (CBD) stents, presenting with recurrent jaundice and undergoing successful open CBD exploration and Roux-en-Y hepaticojejunostomy. This report highlights the importance of follow-up after biliary stenting and the surgical challenges associated with retained stents.